Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1080/01431161.2012.717183
|View full text |Cite
|
Sign up to set email alerts
|

Airborne photogrammetry and lidar for DSM extraction and 3D change detection over an urban area – a comparative study

Abstract: . The surface models, generated from the two different 3D acquisition methods, are compared qualitatively and quantitatively as to what extent they are suitable in modelling an urban environment, in particular for the 3D reconstruction of buildings. Then the data sets, which are acquired at two different epochs t 1 and t 2 , are investigated as to what extent 3D (building) changes can be detected and modelled over the time interval. A difference model, generated by pixel-wise subtracting of both DSMs, indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 26 publications
(24 reference statements)
0
64
0
1
Order By: Relevance
“…Thus, the roughness index can be applied to differentiate false alarms caused by trees. In the work of Pang et al [35] and Stal et al [45], a plane filter and roughness index were employed to remove the vegetated areas, respectively. However, since building roofs may be more complex, especially for a skyscraper, it is almost impossible to fit planes or calculate the roughness as the index.…”
Section: Positive Building Change Results Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the roughness index can be applied to differentiate false alarms caused by trees. In the work of Pang et al [35] and Stal et al [45], a plane filter and roughness index were employed to remove the vegetated areas, respectively. However, since building roofs may be more complex, especially for a skyscraper, it is almost impossible to fit planes or calculate the roughness as the index.…”
Section: Positive Building Change Results Refinementmentioning
confidence: 99%
“…However, there is limited research focused on building change detection using old aerial images and new LiDAR data. Relevant research can be found in Stal et al [45], who employed airborne photogrammetry and LiDAR to extract DSMs for detecting the 3D changes over an urban area. Their major focus was to compare the performance and feasibility of using airborne photogrammetry and LiDAR techniques for 3D surface modeling, and extracting 3D building changes information were only performed using DSM differencing.…”
Section: Introductionmentioning
confidence: 99%
“…For spatiotemporal modeling, by modeling and comparing a cityscape at different time snapshots, a final 3D building change model map, which shows the destructed and newly constructed buildings, can be acquired. Based on the 3D change map, the volume and surface of the building changes were quantified [40]. In addition, a spatiotemporal GIS model was built to study changes in the physical form of cities by visualizing the dynamic transition of the 3DCM over time [41].…”
Section: Discussion Of Studies Of Urban Issues Underpinned By Simplifmentioning
confidence: 99%
“…Height change reflects the main change of buildings and elevation information is an important index for extracting building change information (Stal et al, 2013). High precision DSM can be generated by LiDAR data and building height change can be obtained through DSM differencing, then new or demolished buildings can be detected (Alobeid et at., 2011).…”
Section: Methodsmentioning
confidence: 99%